Analysis Of Employee Performance PT.Tri Digi Fin - Seifal Rezaldin; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This research applies a qualitative descriptive method with the aim of describing and analyzing the issues found. This qualitative approach is based on collecting primary and secondary data. Primary data in this research was obtained through observation, interviews, and documentation, while secondary data was obtained through books, previous research, and articles relevant to this research. The data source in this research is interview transcripts obtained from a number of respondents called research informants. The informants were selected based on a certain method because their abilities or positions were deemed to be able to describe the problem that would be the object of research. There were four informants for this research, consisting of three general staff and one administrative staff. The main objectives of this research are to find out employee performance programs that have been implemented to improve PT Tri Digi Fin, find out about continuous training and development to improve their performance, and find out how employees improve their work performance. The results of this research show that respondents responded to the questions asked by researchers regarding employee performance. When interviewed by researchers, employees revealed that our program performance includes regular assessments based on KPIs (Key Performance Indicators) that help identify areas for improvement. This finding is reinforced by interview results which show that employees who cannot adapt to change or are open-minded to new ideas and improvements can perform less well in a dynamic environment.